PELATIHAN EKONOMI KREATIF DIKALANGAN PELAKU UMKM DI KABUPATEN ENREKANG - Razak, Nurlaely; Data, Muhammad Umar; Madya, Erniwaty Madya; Syafruddin, Muhammad; Djunaid, Rusli; Nur Hamiddin, Muhammad Irwan; Aswad, Abul; Gusmin, Gusmin; Rifandi, Rizky; Tafsiir, Muhammad (STKIP Persada Khatulistiwa Sintang, 2022)
ABSTRACTThe purpose of this activity is to increase the understanding and ability of business actors towards the creative economy. This activity was carried out in Enrekang district, South Sulawesi. The activities were carried out in the form of counseling and dialogue where the speakers came from academics and students of STIEM Bongaya Makassar and were carried out for 1 day. The implementation method is carried out by counseling and discussion groups as well as mentoring which will be carried out in the future when the participants begin to implement the creative economy in their business activities. It is hoped that this activity will develop the creative industry in Enrekang district. It is also hoped that the active role of the Enrekang district government is to provide support and assistance to creative economy actors.Keywords: Creative economy, business actors, training, academicsABSTRAKÂ Tujuan kegiatan ini adalah untuk meningkatkan pemahaman dan kemampuan para pelaku usaha terhadap ekonomi kreatif. Kegiatan ini dilaksanakan di kabupaten Enrekang, Sulawesi Selatan. Pelaksanaan kegiatan dilakukan dalam bentuk penyuluhan dan dialog dimana pematerinya berasal dari kalangan akademisi dan mahasiswa STIEM Bongaya Makassar dan dilakukan selama 1 hari. Metode pelaksanaannya dilakukan dengan penyuluhan dan grup diskusi serta pedampingan yang akan dilakukan pada waktu yang akan datang ketika para peserta mulai mengimplentasi kan ekonomi kreatif dalam kegiatan usahanya. Diharapkan kegiatan ini akan mengembangkan industri kreatif di kabupaten Enrekang.Dab diharapkan juga peran aktif dari pemerintah kabupaten Enrekang untuk memberikan dukungan dan bantuan kepada para pelaku ekonomi kreatif.Kata kunci : Ekonomi kreatif, pelaku usaha, pelatihan, akademisi